Dysfunctional RNA‐binding protein biology and neurodegeneration in experimental autoimmune encephalomyelitis in female mice. Issue 4 (22nd November 2019) - Salapa, Hannah E.; Libner, Cole D.; Levin, Michael C.
Abstract: Altered stress granule (SG) and RNA‐binding protein (RBP) biology have been shown to contribute to the pathogenesis of several neurodegenerative diseases, yet little is known about their role in multiple sclerosis (MS). Pathological features associated with dysfunctional RBPs include RBP mislocalization from its normal nuclear location to the cytoplasm and the formation of chronic SGs. We tested the hypothesis that altered SG and RBP biology might contribute to the neurodegeneration in experimental autoimmune encephalomyelitis (EAE). C57BL/6 female mice were actively immunized with MOG35‐55 to induce EAE. Spinal cords were examined for mislocalization of the RBPs, heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) and TAR‐DNA binding protein‐43 (TDP‐43), SGs, neurodegeneration (SMI‐32), T cells (CD3), and macrophages (CD68). In contrast to naive mice, mice with EAE showed SG formation ( p < 0.0001) and mislocalization of hnRNP A1 ( p < 0.05) in neurons of the ventral spinal cord gray matter, which correlated with clinical score ( R = 0.8104, p = 0.0253). In these same areas, there was a neuronal loss ( p < 0.0001) and increased SMI‐32 immunoreactivity (both markers of neurodegeneration) and increased staining for CD3 + T cells and IFN‐gamma. These findings recapitulate the SG and RBP biology and markers of neurodegeneration in MS tissues and suggest that altered SG and RBP biology contribute to the neurodegeneration in EAE, which might also apply to the pathogenesis of MS. Abstract : Altered stress granule (SG) and RNA‐binding protein (RBP) biology, including RBP mislocalization from the nucleus to cytoplasm, have been shown to contribute to the pathogenesis of several neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTLD), and most recently, multiple sclerosis (MS). Here, we show that the RBPs, heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) and TAR‐DNA binding protein‐43 (TDP‐43), mislocalize to the cytoplasm of spinal cord neurons from mice with experimental autoimmune encephalomyelitis (EAE). We also demonstrate the formation of SGs in spinal cord neurons from mice with EAE and that there is increased neurodegeneration, including neuronal cell loss, in areas with hnRNP A1 mislocalization. These results suggest that altered RBP biology and SG formation may contribute to neurodegeneration in EAE, which may also apply to the pathogenesis of MS.